Remineralizing Effect of Casein Phosphopeptide–Amorphous Calcium Phosphate and Sodium Fluoride on Artificial Tooth Enamel Erosion: An In Vitro Study - Pirca, Kevin (2019)
Aim: To compare in vitro the remineralizing effect of toothpastes with casein phosphopeptide–amorphous calcium phosphate (FPC–FCA) and sodium fluoride on the artificial erosion of tooth enamel. Materials and methods: For the first phase of artificial erosion, group I was considered as the control group without treatment or erosion. For groups II and IV, the drink was used (Coca-Cola®), for groups III and V, the drink (Inca-Kola®), and the four groups were demineralized four times a day (every 3 hours for 2 minutes) for 5 days. In the treatment phase in groups II and III, brushing was performed with sodium fluoride paste (Colgate®), groups IV and V received brushing with FPC–FCA complex (MiPaste®), and for all groups, the same procedure was performed four times a day (every 3 hours for 5 minutes) for 90 days. At the end, the microroughness of the surfaces of all the groups was evaluated by means of a Rugosimeter (Mitutoyo). Results: It was evidenced that the group of sodium fluoride presented a microroughness of 2.79 μm being the group of least remineralization, but the FPC–FCA complex showed a microroughness of 1.96 μm; however, the control group presented a microroughness of 3.20 μm, and the groups sodium fluoride, FPC–FCA compared to the control group proved to be statistically significant with a p < 0.05. Conclusion: The remineralizing effect of FPC–FCA (MiPaste®) complex proved to be greater than sodium fluoride paste (Colgate®) under artificial enamel erosive conditions. Clinical importance: The results of this research serve as a basis for industries to generate products that have the potential for remineralization against various erosive beverages that are consumed daily.